Dehydroquinate Synthase Directly Binds to Streptomycin and Regulates Susceptibility of Mycobacterium bovis to Streptomycin in a Non-canonical Mode - Wei, Wenping; Qiao, Junjie; Jiang, Xiaofang; Cai, Luxia; Hu, Xiaomin; He, Jin; Chen, Min; Yang, Min; Cui, Tao (Frontiers in Microbiology, 2022)
Antimicrobial resistance (AMR) represents one of the main challenges in Tuberculosis (TB) treatment. Investigating the genes involved in AMR and the underlying mechanisms holds promise for developing alternative treatment strategies. The results indicate that dehydroquinate synthase (DHQS) regulates the susceptibility of Mycobacterium bovis BCG to first-line anti-TB drug streptomycin. Perturbation of the expression of aroB encoding DHQS affects the susceptibility of M. bovis BCG to streptomycin. Purified DHQS impairs in vitro antibacterial activity of streptomycin, but did not hydrolyze or modify streptomycin. DHQS directly binds to streptomycin while retaining its own catalytic activity. Computationally modeled structure analysis of DHQS-streptomycin complex reveals that DHQS binds to streptomycin without disturbing native substrate binding. In addition, streptomycin treatment significantly induces the expression of DHQS, thus resulting in DHQS-mediated susceptibility. Our findings uncover the additional function of DHQS in AMR and provide an insight into a non-canonical resistance mechanism by which protein hijacks antibiotic to reduce the interaction between antibiotic and its target with normal protein function retained.